Effect Of Addition Of Ground Vegetable Oil Seeds On The Storage Stability Of Vacuum Packaged Spent Broiler Breeder Chicken Sausages - Indumathi, J; Shashikumar, M; Bhaskarreddy, G V; Babu, A Jagadeesh; Gnanaprakash, M (Journal of Meat Science, 2023)
Spent broiler breeder chicken sausages were developed by incorporated with 10% level of ground vegetable oilseeds (poppy, sesame and peanut) separately and were stored at refrigeration temperature (4±1°C) under vacuum packaging. The vacuum packaged low fat chicken sausages along with control were analyzed for physico- chemical, microbiological and sensory changes throughout the storage time at regular intervals. Results revealed that the vacuum packaged low fat chicken sausages had significantly (p < 0.05) lower FFA, TBARS, tyrosine values and microbial counts than control throughout storage period. Regardless of formulation, coli forms were not detected throughout the storage period in all vacuum packaged sausages. Among low fat treatments, sausages with ground sesame seed recorded significantly (P
Keywords: Vacuum packaging; Spent hen; Ground vegetable oil seeds; Sausages; Quality